The Role of Social Media in Shaping Teenagers' Social Behavior in the Digital Era - Samsidar, Samsidar (Socious Journal, 2024)
Social media has become an integral part of adolescents' lives in the digital era. The use of platforms such as Instagram, TikTok, and WhatsApp influences the way adolescents interact, form self-identities, and understand social norms. This study aims to analyze the role of social media in shaping adolescents' social behavior, using a qualitative approach through in-depth interviews and participant observation of 20 adolescents in Jambi City. The results showed that social media has positive impacts, such as expanding social networks and increasing self-confidence. However, negative impacts were also identified, including increased risk of cyberbullying, social pressure, and decreased direct social interaction. These findings emphasize the importance of digital literacy and the active role of parents and educators in guiding adolescents to use social media wisely.